Letter (copy) : Food for Spain - Tewson, Vincent
032-0111-001 International. HVT/EAB/DT/586. 7th February, 1939. Mr. W. Schevenels, International Federation of Trade Unions, 9, Avenue D'Orsay, Paris VIIe. Dear Comrade Schevenels, FOOD FOR SPAIN. Further to our conversation on the telephone this morning regarding the consignment of 750 tons of potatoes, I have spoken to the Co-operative Wholesale Society in Manchester and have informed them that you are arranging to make the 150,000 French franc charge for carriage of this consignment. They are informing their Rouen depot accordingly. I am enclosing herewith our cheque for £1,000 from the Spanish fund as promised, and I shall be glad if you will let me have your official receipt in due course. With best wishes, Yours sincerely, Assistant Secretary. Cheque. 292/946/32/111